An Efficient Implementation of Advanced Encryption Standard on the Coarse-grained Reconfigurable Architecture - Nguyen, Hung Kiem; Tran, Tu Xuan (VNU Journal of Science: Computer Science and Communication Engineering; Vol 32 No 2 (2016), 2016)
The Advanced Encryption Standard (AES) is currently considered as one of the best symmetric-key block ciphers. The hardware implementation of the AES for hand-held mobile devices or wireless sensor network nodes is always required to meet the strict constraints in term of performance, power and cost. Coarse-grained reconfigurable architectures are recently proposed as the solution that provides high flexibility, high performance and low power consumption for the next-generation embedded systems. This paper presents a flexible, high-performance implementation of the AES algorithm on a coarse-grained reconfigurable architecture, called MUSRA (Multimedia Specific Reconfigurable Architecture). First, we propose a hardware-software partition method for mapping the AES algorithm onto MUSRA. Second, the parallel and pipelining techniques are considered thoughtfully to increase total computing throughput by efficiently utilizing computing resources of MUSRA. Some optimizations at both loop transformation level and scheduling level are performed in order to make better use of instruction-, loop- and task- level parallelism. The proposed implementation has been evaluated by the cycle-accurate simulator of MUSRA. Experimental results show that the MUSRA can be reconfigured to support both encryption and decryption with all key lengths specified in the AES standard. The performance of the AES algorithm on MUSRA is better than that of ADRES reconfigurable processor and TI C64+ DSP.